Centre procedural volume and adverse in‐hospital outcomes in patients undergoing percutaneous transvenous edge‐to‐edge mitral valve repair using MitraClip® in Germany. (3rd May 2021) - Keller, Karsten; Hobohm, Lukas; Schmidtmann, Irene; Münzel, Thomas; Baldus, Stephan; von Bardeleben, Ralph Stephan
Abstract : Aims: The number of transcatheter mitral valve repair (TMVr) procedures has increased substantially during the last years. A better understanding of the relationship between hospital volume of transcatheter transvenous mitral valve repairs using MitraClip® and patient outcomes may provide information for future policy decisions to improve patient management. Methods and results: We analysed patient characteristics and in‐hospital outcomes for all TMVr procedures using MitraClip® performed in Germany from 2011 to 2017. Hospitals were stratified according to centre volumes and patients were compared for baseline characteristics and adverse in‐hospital events. Overall, 24 709 inpatients were treated during the observational period. Patients treated in centres with a volume of ≤10 procedures annually developed more often pulmonary embolism (odds ratio 2.22, 95% confidence interval 1.19–4.13; P = 0.012) compared to those treated in centres with a volume of >10 procedures annually, whereas no association of centre volume (≤10 or >10) was found with in‐hospital mortality ( P = 0.728). Although patients treated in centres with an annual volume >25 TMVr procedures had higher numbers of comorbidities compared to those treated in centres with an annual volume of ≤25 TMVr procedures, in‐hospital mortality did not differ (3.6% vs. 3.5%, P = 0.485). Similarly, when centre volumes were stratified for ≤50 vs. >50 procedural volumes, no association with in‐hospital mortality was recorded ( P = 0.792). A lower rate of mitral valve surgery after MitraClip® was observed over time, particularly in high‐volume centres. Conclusion: Annual numbers of MitraClip® implantations increased from 2011 to 2017 in Germany, whereas in‐hospital mortality remained stable. Although patients treated in high‐volume centres had a more unfavourable risk profile, in‐hospital mortality was comparable to that of low‐volume centres. Abstract : Centre volumes, absolute numbers of treated patients, in‐hospital mortality, major adverse cardiac and cerebrovascular event (MACCE) rate and percutaneous coronary intervention. Learning curve showing a lower number of mitral valve surgeries in high‐volume centres over the observational period and higher risk of pulmonary embolism in low‐volume centres. CI, confidence interval; OR, odds ratio.